a)
"\\frac{dy}{dx}+xy=y^2e^{\\frac{x^2}{2}}\\sin x\\\\\ny'+xy=y^2e^{\\frac{x^2}{2}}\\sin x"
We divide by "y^2"
"\\frac{y'}{y^2}+\\frac{x}{y}=e^{\\frac{x^2}{2}}\\sin x\\\\"
Replacement
"y^{-1}=z, y=z^{-1}, y'=-z^2\\cdot z'\\\\\n-\\frac{z^{-2}z'}{z^{-2}}+xz=e^{\\frac{x^2}{2}}\\sin x\\\\\n-z'+xz=e^{\\frac{x^2}{2}}\\sin x\\\\\ni) -z'+xz=0\\\\\n\\frac{dz}{dx}=xz\\\\\n\\frac{dz}{z}=xdx\\\\\nln|z|=\\frac{x^2}{2}+ln|c|\\\\\nz_0=c\\cdot e^{\\frac{x^2}{2}}\\\\\nii) z=c(x)\\cdot e^{\\frac{x^2}{2}}\\\\"
Input "z" in the equation "-z'+xz=e^{\\frac{x^2}{2}}\\sin x"
"-c'e^{\\frac{x^2}{2}}-xe^{\\frac{x^2}{2}}c+xe^{\\frac{x^2}{2}}c=e^{\\frac{x^2}{2}}\\sin x\\\\\nc'=-\\sin x\\\\\nc=\\cos x+c_1"
then "z=(\\cos x+c_1)e^{\\frac{x^2}{2}}"
or "y^{-1}=(\\cos x+c_1)e^{\\frac{x^2}{2}}"
and solutoin of equation is function
"y=0"
b)
"y_1(x)=\\frac{1}{x}\\\\\n2x^2y''+3xy'-y=0"
for equation
"a_0(x)y''+a_1(x)y'+a_2(x)y=0"
used formula Ostrohrad-Liouville
"\\begin{vmatrix}\n y_1 & y_2 \\\\\n y'_1 & y'_2\n\\end{vmatrix}=ce^{-\\int \\frac{a_1(x)}{a_0(x)}dx}"
in our case
"a_0(x)=2x^2, a_1(x)=3x, a_2(x)=-1"
then
"\\begin{vmatrix}\n y_1 & y_2 \\\\\n y'_1 & y'_2\n\\end{vmatrix}=ce^{-\\int \\frac{3x}{2x^2}dx}\\\\\ny_1y'_2-y'_1y_2=ce^{- \\frac{3}{2}\\int\\frac{1}{x}dx}\\\\\ny_1y'_2-y'_1y_2=ce^{- \\frac{3}{2}ln|x|}\\\\\ny_1y'_2-y'_1y_2=cx^{- \\frac{3}{2}}"
Divide by "y_1^2"
"\\frac{y_1y'_2-y'_1y_2}{y_1^2}=cx^{- \\frac{3}{2}}x^2\\\\\n(\\frac{y_2}{y_1})'=cx^{\\frac{1}{2}}\\\\\n\\frac{y_2}{y_1}=\\int cx^{\\frac{1}{2}}dx\\\\\n\\frac{y_2}{y_1}=\\frac{2}{3}cx^{\\frac{3}{2}}+c_1"
Then the solution of equation is
"y=(\\frac{2}{3}cx^{\\frac{3}{2}}+c_1)\\frac{1}{x}"
or
"y=\\frac{2}{3}cx^{\\frac{1}{2}}+c_1\\frac{1}{x}"
So second linearly independent solution of the equation is
"y_2=\\frac{2}{3}x^{\\frac{1}{2}}"
Comments
Leave a comment